Marginal returns to talent for material risk takers in banking - Moritz Stieglitz; Konstantin Wagner (Halle Institute for Economic Research (IWH), 2020)
Economies of scale can explain compensation differentials over time, across firms of different size, different hierarchy-levels, and different industries. Consequently, the most talented individuals tend to match with the largest firms in industries where marginal returns to their talent are greatest. We explore a new dimension of this size-pay nexus by showing that marginal returns also differ across activities within firms and industries. Using hand-collected data on managers in European banks well below the level of executive directors, we find that the size-pay nexus is strongest for investment banking business units and for banks with a market-based business model. Thus, managerial compensation is most sensitive to size increases for activities that can easily be scaled up.
urn:nbn:de:gbv:3:2-127618
Keywords: G21; G24; G34; 330; banks; business models; marginal returns to talent